Supplementation of bangun-bangun leaf (Coleus amboinicus Lour) and Zn-vitamin E to improve metabolism and milk production of Etawah cross bred goats - Rumetor, Sientje Daisy; Jachja, Jajat; Widjajakusuma, Reviany; Permana, Idat Galih; Sutama, I Ketut (Indonesian Animal Sciences Society, 2008)
Two experiments were conducted to determine the effects of Coleus amboinicus L. and zinc-vitamin E supplementation in ration to improve rumen metabolism and milk production of Etawah crossbred goat. In the first experiment, 6 treatments were evaluated using in vitro batch culture. It was found that Coleus amboinicus and Zn-vitamin E supplementation significantly (P< 0.01) increase dry matter (DM) and organic matter (OM) digestibility and Volatile Fatty Acid (VFA) concentration, but decrease NH3 concentration, rumen pH and total microbe. In the second experiment, 8 treatments were evaluated using in vivo experiment on 24 goats. The result showed that Coleus amboinicus and Zn-vitamin E supplementation significantly increase dry matter and TDN intake and milk production. Key Words: Coleus Amboinicus, Zn-Vitamin E, Rumen Metabolism, Milk Production, Etawah Crossbred Goat